Hasan Langgulung's View of the Family's Role in Children's Religious and Social Education - Putra, Adi (AGENDA: Jurnal Analisis Gender dan Agama, 2022)
The necessity of this study is to clarify the part played by families in children's religious and social upbringing, according per Hasan Langgulung. This kind of study is known as library research. Research that tries to describe or characterize and analyze the function of the family in the religious and social education of children is employed in this discussion as the character study approach, according to Hasan Langgulung. The secondary data source used by the author in this study is taken from the book that contains the subject character. The findings of this study demonstrate that, in accordance with Hasan Langgulung, families should provide children with high-quality religious and social instruction.